Assessment of Learning Disabilities for Future Implications of Physical Education Students - Alamgir Khan; Muhammad Zafar Iqbal Butt; Muhammad Jamil (The Sky)
The present study aimed to assess the learning disabilities of physical education students and to suggest future implications. The study population comprised all the students of sports sciences and physical education (SSPE), University of the Punjab, Lahore, Pakistan. Thus, three hundred students were taken as samples using available sampling techniques. For the collection of data, a Likert-type scale comprised of questions about four different learning disabilities, i.e. dysgraphia, dyscalculia, dyspraxia and dyslexia. The gathered data were administered through the statistical package for social sciences (SPSS, version-26); thus, pertinent statistical tools were used for analysis. After data analysis, the researcher concluded that dyscalculia as learning was the most common learning problem among the students. Based on the conclusion, the researcher recommended that sports sciences and physical education students need special attention in mathematical activities compared to all other academic subjects.